Explaining investment decisions towards cryptocurrencies - Hiillos, Jussi-Petteri (My University, 2021)
Interest towards cryptocurrencies has grown significantly over the last years when people and institutions have started to treat them more as an investable asset class. However, as an asset class, cryptocurrencies are often seen as controversial because of the high volatility, speculation and lack of universally accepted regulation. Even though, the research around cryptocurrencies has increased significantly during the past years, the research around cryptocurrency investors has not achieved notable interest among the academics. Thus, the purpose of this study is to shed light on to that unsolved issue by studying the factors that may have contributed to the past investment decision towards cryptocurrencies. The main factors that were selected for answering the main research question include investment motives, financial risk tolerance and behavioral biases in investment decision making. Behavioral biases that were selected for this study include overconfidence, herding, familiarity/home bias and mental accounting. In addition, background variables and previous investment decisions are used for providing additional explanations for the investment decisions. This study is quantitative by its nature and chosen research method is quantitative web survey. The target population is Finnish speaking retail investors and sample size 872 responses. The results from the empirical part indicate that motives in general do not explain the investment decision towards cryptocurrencies but instead there are other unknown motives that do. Higher financial risk tolerance score was found to be a significant predictor of positive investment decision towards cryptocurrencies. However, based on the results behavioural biases in investment decision making did not explain the investment decision towards cryptocurrencies. From the background variables, only gender (male), investment experience (2-5 years) and average time horizon (1-5 years) had significant impact on the positive investment decision towards cryptocurrencies. Furthermore, cryptocurrency investors were found to have had significantly more likely investments in listed stocks, ETFs, currencies, commodities, derivates and other investments during the previous year prior to the data collection. On the other hand, cryptocurrency investors had invested significantly less likely to investment funds.

Kiinnostus kryptovaluuttoja kohtaan on kasvanut merkittävästi viime vuosina, kun ihmiset ja instituutiot ovat alkaneet kohdella niitä enemmän sijoituskelpoisena omaisuusluokkana. Omaisuusluokkana kryptovaluuttoja pidetään kuitenkin usein kiistanalaisina suuren volatiliteetin, keinottelun ja yleisesti hyväksytyn sääntelyn puutteen vuoksi. Vaikka kryptovaluuttoihin kohdistunut tutkimus on lisääntynyt merkittävästi viime vuosina, kryptovaluuttasijoittajia koskeva tutkimus ei ole saavuttanut merkittävää kiinnostusta tutkijoiden keskuudessa. Näin ollen tämän tutkimuksen tarkoituksena on valottaa tätä ratkaisematonta asiaa tutkimalla tekijöitä, jotka ovat saattaneet vaikuttaa aiempiin sijoituspäätöksiin kryptovaluuttojen osalta. Tärkeimmät päätutkimuskysymyksen selittämiseksi valitut tekijät ovat sijoitusmotiivit, taloudellinen riskinsietokyky ja behavioraaliset harhat sijoittajan päätöksenteossa. Tähän tutkimukseen valittuja behavioraalisia harhoja ovat liika itsevarmuus, laumakäyttäytyminen, tuttuuden harhat ja mentaalitilinpito. Lisäksi sijoituspäätöksiä tutkitaan taustamuuttujien ja aiempien sijoituspäätösten avulla. Tämä tutkimus on luonteeltaan määrällinen ja valittu tutkimusmenetelmä on kvantitatiivinen verkkokysely. Kohderyhmänä ovat suomenkieliset yksityissijoittajat ja otoskoko 872 vastausta. Empiirisen osan tulokset osoittavat, että motiivit eivät yleisesti selitä sijoituspäätöksiä kryptovaluuttoihin, vaan on muita tuntemattomia motiiveja, jotka selittävät. Korkeamman taloudellisen riskinsietokyvyn todettiin ennustavan merkittävästi positiivista sijoituspäätöstä kryptovaluuttoja kohtaan. Toisaalta taas sijoituspäätöksissä läsnä olevien behavioraalisten harhojen perusteella ei kuitenkaan voida selittää sijoituspäätöksiä kryptovaluuttoja kohtaan. Taustamuuttujista vain sukupuolella (mies), sijoittajankokemuksella (2–5 vuotta) ja keskimääräisellä sijoitus aikajänteellä (1–5 vuotta) oli merkittävä vaikutus positiiviseen sijoituspäätökseen kryptovaluuttojen osalta. Lisäksi kryptovaluuttasijoittajilla todettiin olevan huomattavasti todennäköisemmin sijoituksia pörssi osakkeisiin, ETF-rahastoihin, valuuttoihin, hyödykkeisiin, johdannaisiin ja muihin sijoituksiin tiedonkeruuta edeltävänä vuonna. Toisaalta kryptovaluuttasijoittajat olivat sijoittaneet huomattavasti epätodennäköisemmin rahastoihin.
Keywords: financial risk tolerance, behavioral biases, investment motives, investment decision making, cryptocurrencies